Strategi Pemasaran UMKM Iniceker Malang dengan Metode SWOT dan QSPM - Kristiana Yolanda Febrillyant; Purnomo Purnomo (Teknik Industri Universitas Ma Chung, 2021)
Iniceker is a food and beverage that specializes in selling chicken feet, but the company faces marketing-related problems that hinder its growth and development. This study aims to determine optimal marketing strategies that can be applied to Iniceker for sustainability during and after the pandemic. The research was conducted using the SWOT analysis and QSPM approach. The study identified two alternative marketing strategies: market development and product development. These alternatives were chosen based on the analysis of internal and external factors affecting the business. Market development aims to expand the target market by improving the business's visibility and reputation, targeting new customers, and increasing sales. Product development focuses on improving the quality of the product and introducing new varieties to attract customers. It is expected that the implementation of the chosen marketing strategies will help Iniceker overcome its current marketing-related problems, increase its sales, and expand its business.